Awareness and utilization of modern contraceptives among street women in North-West Ethiopia - Megabiaw Berihun (BMC, 2012)
Abstract Background Contraception is a major component of reproductive health. Assessing the levels of contraceptive awareness and use helps to identify potential areas of intervention. Hence, this study was conducted to assess awareness, practice and associated factors of modern contraceptives among street women in North-West Ethiopia. Methods A cross-sectional study was conducted on 204 street women from Gondar and Bahir Dar cities. Participants were recruited from "cluster" sites such as main road sides, isolated slum areas, around Churches and/or Mosques (in the mornings of Sundays and other religious feast days) and streets where street women usually reside and/or sleep. Data were collected using a pre-tested and structured interview questionnaire in local language (Amharic) after informed verbal consent. Data were then entered into SPSS version 16.0 for analysis. Binary logistic regression models were fit to assess associations and control confounding. Associations were measured by the Odds ratio and its 95% confidence interval. Results The mean (±SD) age of participants was 30.9 (± 8.7) years. Majority (90.7%) had ever heard about modern contraceptives. Nearly half (47.1%) had ever used and a third (34.3%) were current users. Three quarter of the current users (74.3%) were using injectables while 10% were on long acting or permanent methods. Marital status (AOR=2.81), family size (AOR=2.67) and age of 25-34 years (AOR=3.45) were associated with modern contraceptive use. Conclusions Current contraceptive use among street women is satisfactory considering their life styles and living conditions. However, further research is required to explain perceptions and hidden barriers.